Mobility within Europe - The Attitudes of European Youngsters - Michael Fertig; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2003)
Intensified European integration,enlargement of the EU,and increasing migration activity worldwide have pushed migration and migration policy to the forefront of the European agenda.While many observers hesitate to embrace immigration emanating from outside Europe,sectoral skill shortages and social security systems under demographic pressure have fostered an almost unanimous call for larger mobility within Europe.Yet, neither does intra-European migration respond to this request,nor are the possible consequences of increased migration activity well understood.This paper embeds this discussion into a systematic classification of economic migration research according to its major conceptual and applied questions. The state of theoretical and empirical research in this literature is reviewed briefly,with a focus on intra-European migration.We conclude that the relatively positive assessment of this type of migration mainly derives from its high skill content.To prepare the prediction of future developments,we offer empirical evidence on the determinants of intra-EU-migration by an analysis of the Eurobarometer survey.Unless information deficits,traces of xenophobic tendencies,and the perception of prohibitively high levels of bureaucratic red tape are overcome,intra-European migration will not play the role it is hoped for.
Keywords: J61; F22; 330; Labor mobility; migration intention; intra-EU-migration; Internationale Arbeitsmobilität; Internationale Wanderung; Freizügigkeit; Binnenwanderung; EU-Staaten